Upaya Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Membatik Jumputan - Rofiah, Sohibah Darojatur; Mangkuwibawa, Hilman (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2020)
This study aims to determine the fine motor skills of children before using activities membatik jumputan, to determine the learning process in children when using jumputan batik activities, to determine the child's fine motor skills after using jump batik making activities each cycle. This research method uses the classroom action research (CAR) method with a mixed approach. The subject of this research is group B RA Annur Pungangan Kab. Subang as many as 30 students. Data collection techniques in this study used observation sheets of teacher and student activities, observation sheets of fine motor skills, and documentation. Based on research class action carried out in RA Annur regency. Subang, it can be concluded that the fine motor abilities of children before the application of batik making jumputan with very little criteria. As for the cycle I obtained an average value of 49.43 with a criterion of very less turns out to have increased in the second cycle obtained an average value of 74.23 with good criteria. Based on the results of the study proved that the achievement of students by using activities batik making jumps can improve children's fine motor skills